The impact of Teaching Sustainable Development Principles on the Design Performance of Students Studying Fashion Design - Habibeh Rezvani Ahangar kolaee; Farideh Talebpour; shaahin Javadi (پژوهش‌های برنامه و توسعه)
The purpose of this research work was to evaluate the impact of sustainable development principles on the design performance of students studying fashion design using a four-group experimental design with pre-test and post-test. In this regard, 87 students were selected from the last semester students in the field of textile design and clothing design and sewing in Dr. Shariati Vocational and Technical Girls College and were divided into four groups. Two groups were selected as experimental group and two as control group to be included in Solomon's four-group design. The teaching of the principles of sustainable development and its importance in fashion design for students were taught over a three-week period but were not taught in the control group classes. Then the results of the research data were analyzed using inferential statistics including analysis of variance and covariance. The results show that teaching the principles of sustainable development in the textile and apparel industry to undergraduate students of textile design and undergraduate design and sewing improves their cognitive performance in sustainable apparel design in order to reduce waste. Therefore, presenting a curriculum that includes a sustainable garment design seminar and workshop can improve students' awareness of the life cycles of fibers, textiles and garments and their environmental impacts on the fashion design and in this way, it will help to achieve sustainable development in the country.